Visual-motor response indices versus individual performances in basketball - Losin, B. E.; Larionova, M. N.; Bobrov, I. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to test and analyze the individual age-, gender and skills-specific visual motor response rates versus the competitive performances.